1999
DOI: 10.1007/bf03218026
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve repair by Carpentier-Edwards Physio annuloplasty ring

Abstract: A semi-flexible annuloplasty ring (Physio-ring) was clinically used in 30 cases of mitral valve insufficiency. The Physio-ring has the characteristics in which the anterior section is rigid and has a saddle-shaped curve, while the posterior section is flexible to allow for changes in size and shape of the anulus during ventricular contraction. The patients were aged from 23 to 73 years (mean 53.8 +/- 12.5). The cause of mitral valve insufficiency was degenerative (in 24 patients), rheumatic (2), ischemic (1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Carpentier and colleagues 5 published their results in 1995, showing that in 137 patients followed up for 18 months, only 6.8% had residual mild MR and none required re-operation. Kurosawa and colleagues 8 also had excellent results in a series of 30 patients, with none requiring redo surgery and only 3.4% with residual MR at 6 months. Sousa and colleagues 7 found that 2 of 100 patients required re-operation for systemic anterior motion following mitral annuloplasty, and 15 had mild residual MR at 19 months.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Carpentier and colleagues 5 published their results in 1995, showing that in 137 patients followed up for 18 months, only 6.8% had residual mild MR and none required re-operation. Kurosawa and colleagues 8 also had excellent results in a series of 30 patients, with none requiring redo surgery and only 3.4% with residual MR at 6 months. Sousa and colleagues 7 found that 2 of 100 patients required re-operation for systemic anterior motion following mitral annuloplasty, and 15 had mild residual MR at 19 months.…”
Section: Discussionmentioning
confidence: 86%
“…5 Although previous studies have demonstrated the feasibility and effi ciency of repair with the Physio ring, only a few have reported mid-and long-term results. [6][7][8] The aim of this study was to evaluate the mid-term results of annuloplasty with this ring.…”
Section: Introductionmentioning
confidence: 99%
“…Kurosawa et al reported short-term outcomes with a low in-hospital mortality (3.3%). 16 The higher mortality rate could be due to different inclusion criteria, which allowed further concomitant procedures (e.g., bypass surgery). They reported a MVA of 2.61 AE 0.82 cm 2 , which is slightly smaller than in our series; this could be attributed to the more round form of the CE Physio II Ring.…”
Section: Prior Studiesmentioning
confidence: 99%
“…Among the techniques used in MV repair, ring annuloplasty has been proposed as a method to reshape the mitral annulus and reduce MR recurrence [5]. However, a consensus has not yet been reached regarding the best choice of annuloplasty, specifically between complete rings and partial bands, and the selection of semi-rigid or rigid materials [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%